Noc jak Almone. Uwagi o mitologii i dekolonizacji Pierwszego Snu Sor Juany Inés de la Cruz - Czarnecki, Łukasz (Humaniora. Czasopismo Internetowe, 2026)
The aim of this article is to analyze the first part of Sor Juana Inés de la Cruz’s poem First Dream from the perspective of philosophical reflection on Greco-Roman mythology, interpreted through the prism of Ovid’s Metamorphoses, but approached from a postcolonial perspective. The main research question is: what function does mythology serve in Sor Juana’s work in the context of postcolonial interpretation? The hypothesis posits that the Tenth Mexican Muse, aware of her situation within the colonial system of New Spain, makes a creative effort to transcend the imposed limitations. The form of this liberation is a dialogue with classical tradition and the practice of creative reading, allowing her to transform European models.